2009
DOI: 10.1002/arch.20312
|View full text |Cite
|
Sign up to set email alerts
|

The importance of starch and sucrose digestion in nutritive biology of synanthropic acaridid mites: α‐Amylases and α‐glucosidases are suitable targets for inhibitor‐based strategies of mite control

Abstract: The adaptation of nine species of mites that infest stored products for starch utilization was tested by (1) enzymatic analysis using feces and whole mite extracts, (2) biotests, and (3) inhibition experiments. Acarus siro, Aleuroglyphus ovatus, and Tyroborus lini were associated with the starch-type substrates and maltose, with higher enzymatic activities observed in whole mite extracts. Lepidoglyphus destructor was associated with the same substrates but had higher activities in feces. Dermatophagoides farin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
(38 reference statements)
4
14
0
Order By: Relevance
“…A similar situation was observed for bacteriolytic and starch-degrading activities (Erban and Hubert, 2008;Erban et al, 2009). This means that many L. destructor gut enzymes are produced in very large amounts in comparison with the rest of the mite species studied.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…A similar situation was observed for bacteriolytic and starch-degrading activities (Erban and Hubert, 2008;Erban et al, 2009). This means that many L. destructor gut enzymes are produced in very large amounts in comparison with the rest of the mite species studied.…”
Section: Discussionsupporting
confidence: 75%
“…Some influences of protein addition into the diets were observed in T. putrescentiae and A. siro, which showed only intermediate protease activities, but the effect on population increase was very low. A similar small effect on population increase was observed on the addition of starch into diets (Erban et al, 2009). The results showed that the nutritional benefit from bacterial cells was higher than from pure proteins (Erban and Hubert, 2008).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The use of chromogenic substrates for the visualization of digestive processes has been tested previously using starch azure and Micrococcus lysodeikticus for the localization of a-amylase and bacteriolytic activity in mites, respectively (Erban and Hubert, 2008;Erban et al, 2009). Recently, the digestive activity of proteases in the (B) a specimen fed the ZRRpNA (P138) chromogenic substrate; the empty arrows point to the yellow color in the colon and postcolon, and the black arrows point to mesenteric cells containing substrate inside granulae; (C) total view of specimens fed the cathepsin H (A2027) fluorescent substrate; the arrows point to areas with high concentrations of fluorescent markers; (D) specimens fed the ArgpNA (P136) chromogenic substrate; the empty arrows point to the yellow color in the colon and postcolon; the black arrows point to mesenteric cells containing substrate inside granulae; (E, F) specimens fed the cathepsin D (C6983) fluorescent substrate; (E) total view, with arrows pointing to areas with high concentrations of fluorescent marker; (F) detailed view of the mesodeum, with arrows pointing to areas with high concentrations of fluorescent markers in food boli in the colon and in the postcolon; (G, H) specimens fed MAAPMpNA, indicating cathepsin G activity; (G) total view; (H) detailed view, with black arrows pointing to mesenteric cells that contain substrate inside of granulae.…”
Section: Discussionmentioning
confidence: 99%